2017
DOI: 10.5539/ijbm.v12n2p207
|View full text |Cite
|
Sign up to set email alerts
|

Building Employee Brand Equity to influence Organization Attractiveness and Firm Performance

Abstract: This paper explores the various dimension of Internal Branding like training, orientation and briefing and Brand supporting behavior (like brand allegiance, brand endorsement and brand citizen behaviour).It further explores impact of Internal branding (IB), Brand commitment (BC) and Brand supporting behavior BSB) on Organization attractiveness (OA) and Firm Performance (FP). The study shows that Internal Branding (IB), Brand commitment (BC) and brand supporting behavior (BSB) impact Organizational attractivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Our findings reveal that OA has a direct effect on the performance level of SQP to hospital patients. This finding is supported in previous research showing that OA has an impact on firms’ performance [32]. A practical implication of this is the importance for hospital managers to actively “control” the level of frontline employees’ perception of OA, and to take whatever steps are needed to develop, maintain, or increase OA to ensure that it keeps within a (positive) zone of tolerance.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our findings reveal that OA has a direct effect on the performance level of SQP to hospital patients. This finding is supported in previous research showing that OA has an impact on firms’ performance [32]. A practical implication of this is the importance for hospital managers to actively “control” the level of frontline employees’ perception of OA, and to take whatever steps are needed to develop, maintain, or increase OA to ensure that it keeps within a (positive) zone of tolerance.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, based on social-identity theory, when frontline employees identify positively with their organization, in addition to EG, it drives frontline employee SQP to hospital patients. Finally, previous research has also found that OA has a positive effect on firm performance [32]. Which brings us to our third hypothesis: Hypothesis 3: Organizational attractiveness is positively related to employee service quality provision.…”
Section: Conceptual Modelmentioning
confidence: 66%
“…In summary, based on this argument, the measuring tools implemented to evaluate job satisfaction in an organization differ based on the type of the organization itself and its service processes within the internal marketing philosophy (George, 1990;Vavra, 1992). Moreover, its observed that shared factors are effecting on employees performance from human resources perspectives as well as Dahl and Peltier (2014); Yao, Chen, and Cai (2013); Kashive and Khanna (2017); Lussier and Hendon (2018).…”
mentioning
confidence: 93%
“…On the other hand, we must bear in mind that the attractiveness of the organization has a significant impact on the employee's perception of the company's performance [4]. As such, this aspect may play a relevant part in the decision to send an employment application to the firm.…”
Section: Introductionmentioning
confidence: 99%